A double-sided cadmium telluride thin-film solar cell and a method for manufacturing the same
Patent Information
- Application Number
- CN202610970773.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-01
AI Technical Summary
[0007]本发明针对现有超薄(<1 μm)碲化镉吸收层在长波段(700~860 nm)吸收率不足70%、且传统陷光结构往往牺牲背面透光性的问题,提出一种创新结构:通过在前界面引入导模共振光栅,在背面设计光栅型金属背电极,形成光学谐振与耦合机制,实现对入射光的高效管理与利用
1、本发明针对超薄吸收层(厚度<1 μm)在长波段(700~860 nm)吸收率普遍低于70%的问题,本结构通过前侧导模共振光栅与背侧光栅型金属背电极的协同光学设计,有效增强光在吸收层内的局域与多次散射,显著提升光程和吸收效率,尤其改善了长波响应,使全波段吸收得到整体优化。
Smart Images

Figure CN122476740B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cadmium telluride thin-film solar cell technology, and particularly to a bifacial cadmium telluride thin-film solar cell and its preparation method. Background Technology
[0002] Cadmium telluride (CdTe) thin-film solar cells have become an important technological route in large-scale ground-mounted power plants and building-integrated photovoltaics (BIPV) due to their advantages such as low manufacturing cost, good low-light response, and strong high-temperature stability. With the increasing industry demand for reducing material costs and expanding application scenarios, the development of ultra-thin (absorber layer thickness < 1 μm) CdTe cells with bifacial power generation capabilities has become a clear technological trend. However, existing technologies face multiple bottlenecks in achieving this goal, constrained by the interplay of material, optical, and electrical properties, severely limiting performance improvement and industrialization.
[0003] Firstly, regarding the back electrode material and structure, existing bifacial cadmium telluride solar cells generally use indium tin oxide (ITO) as the transparent back electrode, but this faces dual limitations in resource cost and photoelectric performance. On the one hand, indium (In), a key component of ITO, has extremely low abundance in the Earth's crust (approximately 0.001 ppm), making the raw material expensive (>300 USD / kg), resulting in the electrode accounting for more than 30% of the cost of the solar cell module. On the other hand, there is an inherent contradiction between the transmittance and conductivity of the ITO thin film: to achieve a back transmittance of >80%, the ITO layer thickness needs to be reduced to below 100 nm, at which point its sheet resistance increases sharply to >100 Ω / m². This leads to a significant increase in series resistance and a decrease in fill factor (FF) of more than 5%; while increasing the ITO thickness can achieve a low resistivity (<10). -3 If the transmittance is less than Ω·cm, the transmittance will drop sharply to below 40%, severely limiting the bifacial factor of the battery (usually below 75%). This contradiction of "high transmittance - low resistance" is particularly prominent when using low-temperature deposition processes.
[0004] Secondly, regarding the optical management of ultrathin absorption layers, while reducing the CdTe layer thickness to 0.8~1μm can significantly reduce raw material consumption and reduce bulk recombination, it results in reduced light absorption capacity, especially for long-wavelength photons >600nm, with an absorption rate of less than 70%. Traditional light-trapping techniques, such as fabricating textured glass or using a ZnTe:Cu back reflector layer, can enhance the capture of front-incident light, but both come at the cost of completely sacrificing back-side transmittance, making them unsuitable for applications requiring double-sided light reception.
[0005] Furthermore, in terms of process compatibility, the high-temperature fabrication process of transparent conductive oxide (TCO) back electrodes easily induces grain boundary degradation and metal impurity diffusion in the cadmium telluride absorber layer, leading to an increase in the interfacial recombination current density (J0) to 50 fA / cm². 2 The above results in open-circuit voltage loss. If low-temperature deposition is used to avoid thermal damage, it is difficult to simultaneously obtain TCO films with both high transmittance and high conductivity.
[0006] It is evident that existing technologies, in pursuing ultra-thin, bifacial CdTe solar cells, are mired in multiple dilemmas, including reliance on scarce materials, the incompatibility between light transmittance and conductivity, the conflict between light-trapping design and bifacial power generation, and the contradiction between process temperature and interface quality. Therefore, developing a novel back electrode structure and its integration scheme that can simultaneously achieve high back-side light transmittance, low resistivity, and efficient light-trapping capability, without relying on scarce materials, has become a core technological problem urgently needing to be solved to promote the industrialization of ultra-thin bifacial CdTe solar cells. Summary of the Invention
[0007] This invention addresses the problem that existing ultrathin (<1 μm) cadmium telluride absorber layers have an absorption rate of less than 70% in the long wavelength range (700~860 nm), and that traditional light-trapping structures often sacrifice back-side transmittance. It proposes an innovative structure: by introducing a mode-guided resonant grating at the front interface and designing a grating-type metal back electrode on the back, an optical resonance and coupling mechanism is formed, achieving efficient management and utilization of incident light. By optimizing the period, size, and morphology of the front and rear gratings, light absorption and carrier collection are synergistically enhanced, increasing short-circuit current density while reducing series resistance and improving the bifaciality factor, ultimately achieving overall optimization of the optical and electrical performance of bifacial cadmium telluride thin-film solar cells. The technical solution provided by this invention is as follows: On one hand, the present invention provides a bifacial cadmium telluride thin-film solar cell, comprising: The cadmium telluride absorption layer has a thickness of 0.8~1.0 μm; A guided-mode resonant grating is disposed on the front side of the cadmium telluride absorption layer, and the guided-mode resonant grating has a first period; The first period is configured to couple the solar spectrum incident from the front side into a guided mode propagating in the cadmium telluride absorption layer through the guided mode resonance effect; the phase matching equation is determined by the guided mode resonance condition. A grating-type metal back electrode is disposed on the back side of the cadmium telluride absorption layer, comprising periodically alternating metal grating lines and light-transmitting gaps, wherein the grating-type metal back electrode has a second period. The second period is configured to be phase-matched with the propagation constant of the guided mode based on the reverse coupling phase matching condition, so as to generate reverse coupling to the guided mode, thereby forming an optical resonant cavity together with the cadmium telluride absorption layer, the guided mode resonant grating and the grating-type metal back electrode to enhance light absorption.
[0008] In one specific implementation, the first period is 300~500 nm; the second period is 600~750 nm.
[0009] In one specific implementation, the guided mode resonant grating is a hexagonal cylindrical grating.
[0010] In one specific implementation, the height of the hexagonal cylindrical grating is 100~200nm and the diameter is 150~300nm.
[0011] In one specific implementation, the material of the guided mode resonant grating is silicon nitride or silicon dioxide.
[0012] In one specific implementation, the grating-type metal back electrode is a parallel grating structure; wherein the linewidth of the metal grating is 210-500nm and the thickness is 50-150nm.
[0013] In one specific implementation, the material of the metal grid wire is selected from one or more of molybdenum, aluminum, chromium, silver, copper, and nickel.
[0014] In one specific implementation, it also includes: A transparent conductive layer and a window layer are sequentially stacked on the front side of the cadmium telluride absorber layer; A back contact layer disposed on the back side of the cadmium telluride absorber layer; The guided mode resonant grating is disposed on the surface of the transparent conductive layer away from the cadmium telluride absorption layer.
[0015] On the other hand, the present invention also provides a method for preparing a double-sided cadmium telluride thin-film solar cell, comprising the following steps: Provide a substrate; A mode-guided resonant grating is formed on the substrate; A transparent conductive layer is deposited on the guided-mode resonant grating and the substrate; A window layer and a cadmium telluride absorption layer are sequentially deposited on the transparent conductive layer, and the cadmium telluride absorption layer is treated with cadmium chloride and annealed. A back contact layer is formed on the cadmium telluride absorber layer after annealing; A grating-type metal back electrode is formed on the back contact layer; The period of the grating-type metal back electrode is configured to match the phase of the propagation constant of the guided mode excited by the guided mode resonant grating in the cadmium telluride absorption layer.
[0016] In one specific implementation, the step of forming the grating-type metal back electrode includes: On the surface of the back contact layer, a metal material is deposited by magnetron sputtering at a substrate temperature not exceeding 80°C to form the grating-type metal back electrode.
[0017] By adopting the above technical solution, the double-sided cadmium telluride thin-film solar cell and its preparation method provided by the present invention have the following beneficial effects: 1. This invention addresses the problem that the absorption rate of ultrathin absorption layers (thickness < 1 μm) is generally less than 70% in the long wavelength range (700~860 nm). This structure effectively enhances the localization and multiple scattering of light in the absorption layer through the synergistic optical design of the front-side guided mode resonant grating and the back-side grating-type metal back electrode, significantly improving the optical path and absorption efficiency, especially improving the long-wavelength response, and thus optimizing the absorption across the entire wavelength range.
[0018] 2. By using a grating-type metal back electrode structure to replace traditional scarce and expensive indium-based transparent conductive materials (such as ITO, whose market price exceeds $300 / kg), this structure achieves high back-side transmittance while maintaining excellent electrical conductivity, thereby significantly reducing the material cost of the battery and alleviating the problem of limited indium resource supply.
[0019] The grating-type metal back electrode is prepared by low-temperature (<80℃) magnetron sputtering process, which avoids the formation of interface defects and diffusion of metal impurities in the traditional high-temperature deposition process, effectively suppresses non-radiative recombination loss, thereby improving the open circuit voltage and fill factor, and ultimately achieving higher photoelectric conversion efficiency.
[0020] 4. Because the grating-type metal back electrode adopts a low-resistance metal grid line design, it can achieve efficient carrier collection while ensuring high light transmittance, significantly reducing series resistance. This structure not only supports efficient utilization of back incident light, but also overcomes the problem of limited performance on both sides caused by the mutual repulsion of light transmittance and conductivity properties in traditional transparent back electrodes. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1This is a schematic diagram of the structure of a double-sided cadmium telluride thin-film solar cell provided in an embodiment of the present invention; Figure 2 A schematic diagram of the structure of a cadmium telluride thin-film solar cell provided as a comparative example of the present invention; Figure 3 This is a schematic diagram of a guided-mode resonant grating (102 layers, hexagonal arrangement) provided in an embodiment of the present invention; Figure 4 This is a schematic diagram of a grating-type metal back electrode (107 layers, arranged in strips) provided in an embodiment of the present invention.
[0023] The following is supplementary explanation of the attached figures: 101-Substrate; 102-Mode-guided resonant grating; 103-Transparent conductive layer; 104-Window layer; 105-Cd telluride absorption layer; 106-Back contact layer; 107-Grate-type metal back electrode. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0025] The term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the invention. In the description of the invention, it should be understood that the terms "upper," "lower," "top," "bottom," etc., indicating orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined with "first" and "second" may explicitly or implicitly include one or more of that feature. Moreover, the terms "first," "second," etc., are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein.
[0026] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to an integer, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included. For example, a specified range from “1 to 10” should be considered to include any and all subranges between the minimum value 1 and the maximum value 10. Exemplary subranges of the range 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, etc.
[0027] This invention achieves efficient light field modulation and carrier collection in ultrathin cadmium telluride solar cells through the synergistic design of a guided-mode resonance (GMR) grating at the front interface and a grating-type metal back electrode 107 at the back interface. Specifically, the period of the GMR grating 102 is configured to couple incident light into a guided mode propagating in the cadmium telluride absorption layer 105 via the GMR effect; the period of the grating-type metal back electrode 107 is configured to match the phase constant of the guided mode, thereby generating reverse coupling to the guided mode. This allows the cadmium telluride absorption layer 105, the GMR grating 102, and the grating-type metal back electrode 107 to collectively form an optical resonant cavity. This synergistic mechanism significantly enhances the capture efficiency of long-wavelength photons and effectively suppresses light escape in submicron-thickness absorption layers. Simultaneously, the grating-type metal back electrode 107 structurally combines a high-transmittance region with a low-resistance conductive metal portion, achieving simultaneous optimization of a transparent back electrode and efficient carrier collection. The use of an ultrathin absorber layer significantly reduces the raw material consumption of cadmium telluride. Experimental results show that, compared with traditional thick-layer cells and ultrathin cells without grating structures, the embodiments of the present invention achieve similar open-circuit voltage, short-circuit current density, and conversion efficiency while significantly reducing the absorber layer thickness to 0.8~1.0 μm, and successfully realize bifacial power generation, thereby expanding the application potential of cadmium telluride solar cells in scenarios such as building-integrated photovoltaics.
[0028] The battery specifically includes: a cadmium telluride absorber layer 105 with a thickness of 0.8~1.0 μm, which, while achieving a significant reduction in absorber layer thickness, still maintains power generation performance comparable to conventional thick layers (3~5 μm), effectively capturing photons in the 400~900nm wavelength band of the solar spectrum and converting them into photogenerated carriers; a guided-mode resonance grating 102, disposed on the front side of the cadmium telluride absorber layer 105, having a first period, which is configured to couple the solar spectrum incident from the front side into guided modes propagating in the cadmium telluride absorber layer 105 through guided-mode resonance effect, with its phase matching equation determined by the guided-mode resonance condition; thereby enhancing the effective optical path and absorption probability of light within the ultrathin absorber layer; and a grating-type metal back electrode 107, disposed on the back side of the cadmium telluride absorber layer 105, composed of periodically alternating metal grid lines and light-transmitting gaps. The metal grid lines are used to achieve low-resistance carrier collection, while the light-transmitting gaps allow light to pass through the back side. Incident light passes through to support the bifacial power generation function of the battery. Its overall grating structure is also configured to have a second period. This second period is determined according to the reverse coupling phase matching condition and is phase-matched with the propagation constant of the guided mode. It can generate reverse coupling to the guided mode, so that the cadmium telluride absorption layer 105, the guided mode resonant grating 102 and the grating-type metal back electrode 107 together form an optical resonant cavity. The absorption of light energy by the cadmium telluride absorption layer 105 is further enhanced through the resonant feedback mechanism. In addition, light incident from the side of the grating-type metal back electrode 107 can pass through the light transmission gap and the back contact layer 106 in sequence to enter the cadmium telluride absorption layer 105, or couple with the resonant cavity mode, thereby realizing the bifacial working characteristics of the battery, which can effectively absorb incident light and generate electricity on both the front and rear sides.
[0029] In one specific implementation, the period of the guided-mode resonance grating 102 is determined by its guided-mode resonance condition, while the period of the grating-type metal back electrode 107 needs to match the guided-mode wave vector excited by the grating to achieve reverse coupling and phase feedback of the guided mode, thereby forming an optical resonance within the absorption layer. Furthermore, when a specific metal material is selected for the back electrode, its period design also needs to consider the introduction and control of surface plasmon resonance coupling effects. In this scheme, the first period (Λ1) is preferably 300~500 nm, and the second period (Λ2) is preferably 600~750 nm. The specific design basis is as follows: The first period Λ of the guided mode resonant grating 102 front Based on the optimized determination of the guided mode resonance condition, its phase matching equation is:
[0030] in: β guided The propagation constant of the excited guided mode is determined by the waveguide structure and material properties, and can be obtained by solving the eigenvalue problem of Maxwell's equations under specific boundary conditions. k0 = 2π / λ is the wave vector of the incident light in vacuum; n eff The effective refractive index of the guided mode (approximately 2.0~2.5 for the CdTe layer); θ is the angle of incidence; m is the diffraction order, usually taken as m=±1.
[0031] The first cycle Λ front The wavelength was optimized to 300~500 nm to match the coupling requirements of the 400~900 nm band in the solar spectrum, achieving high-efficiency optical coupling with wide angle and polarization insensitivity.
[0032] The second period Λ of the grating-type metal back electrode 107 rear Determined based on the reverse coupling phase matching condition:
[0033] in: n is the diffraction order, usually taken as n=±1.
[0034] Second cycle Λ rear The wavelength is designed to be 600~750 nm to achieve precise matching with the guided mode propagation constant.
[0035] The synergistic effect of the guided-mode resonant grating 102 and the grating-type metal back electrode 107 can be expressed as a momentum conservation form:
[0036] Among them: G i =2π / Λ i , is the reciprocal lattice vector of the grating, i.e., G1 = 2π / Λ front G2=2π / Λ rear .
[0037] This momentum matching condition ensures that when the guided mode excited by the guided mode resonant grating 102 propagates to the interface of the grating-type metal back electrode 107, it can generate constructive interference and energy feedback through the periodic modulation of the grating-type metal back electrode 107, thereby forming a Fabry-Perot type resonant cavity in the absorption layer, enhancing the local intensity of the optical field and the effective optical absorption length, and ultimately improving the photoelectric conversion performance of the battery.
[0038] In a specific implementation, please refer to Figure 3 The guided-mode resonance grating 102 is a hexagonal cylindrical grating that achieves broadband and efficient light trapping by exciting the guided-mode resonance effect. This two-dimensional periodic symmetry design has polarization-independent characteristics and wide-angle response capability, and can maintain stable optical performance under arbitrary polarization states and large-angle incident conditions. It is suitable for high-efficiency photoelectric conversion systems with low sensitivity to incident light conditions.
[0039] In one specific implementation, the height of the hexagonal cylindrical grating is 100–200 nm, and the diameter is 150–300 nm. This size range is based on a synergistic optimization of guided-mode resonance conditions and fabrication feasibility. This height range can effectively excite and maintain low-order guided-mode resonance in the visible to near-infrared band, while achieving broadband impedance matching through the subwavelength structure, thereby enhancing light absorption and suppressing reflection. Too low a height will lead to insufficient mode coupling, while too high a height may cause high-order mode interference and increase fabrication difficulty. The selection of the diameter directly affects the grating's equivalent refractive index and fill factor: too small a diameter will result in insufficient equivalent refractive index modulation amplitude, weakening the resonant coupling strength; too large a diameter may cause the grating to tend towards planarization, reducing the scattering and impedance matching effect of the subwavelength structure. Under the premise of ensuring two-dimensional symmetry, this height and diameter range together balance the requirements of optical performance bandwidth, angle, and polarization robustness with the structural fidelity requirements of nanofabrication.
[0040] In one specific implementation, the guided-mode resonant grating 102 is made of silicon nitride (Si3N4) or silicon dioxide (SiO2). Both have moderate refractive indices in the visible to near-infrared band (approximately 2.0 for Si3N4 and approximately 1.45 for SiO2), which can form an effective refractive index contrast with the common substrate material 101, thereby supporting strongly localized guided-mode resonance; at the same time, their low optical loss characteristics ensure the high quality factor of the resonant mode.
[0041] In a specific implementation, please refer to Figure 4 The grating-type metal back electrode 107 adopts a parallel grating line structure; the linewidth of the metal grating line is 210~500nm, and the thickness is 50~150nm. If the linewidth is too small, the cross-sectional area of the metal grating line will be insufficient, the series resistance will increase sharply, the fill factor will be greatly reduced, and the narrow linewidth is prone to process defects (such as broken lines and rough edges). If the linewidth is too large, the proportion of the back light-transmitting area will be too small, and the back power generation gain will be almost lost. At the same time, the excessively wide metal lines will make the grating tend to be flat, destroying its diffraction feedback capability for the guided mode, and the front absorption efficiency will also decrease. If the thickness is too small, the metal film may be discontinuous or have too high resistance, increasing ohmic loss and reducing reflectivity. Although the thickness is too large, the conductivity improvement is limited, but it will waste materials, increase the processing time, and may cause the film layer to peel off or warp due to internal stress.
[0042] In one specific implementation, the metal grid wire is made of one or more of molybdenum, aluminum, chromium, silver, copper, and nickel. Different metals, due to their differences in work function and conductivity, can match the energy level structure of the device and reduce contact resistance, thereby enhancing charge collection efficiency. Simultaneously, highly reflective metals such as silver and aluminum help improve the light reflection and surface plasmon resonance intensity of the back electrode, but require a passivation layer to improve contact. Materials such as chromium and molybdenum, on the other hand, provide better adhesion and environmental stability. Through single-layer or composite-layer designs, this material system can reduce optical losses while ensuring the long-term reliability of the electrode structure and scalable process adaptability.
[0043] In one specific implementation, please refer to Figure 1 The bifacial cadmium telluride thin-film solar cell has a stacked structure that, from front to back, includes: a substrate 101, a mode-guided resonant grating 102, a transparent conductive layer 103, a window layer 104, a cadmium telluride absorption layer 105, a back contact layer 106, and a grating-type metal back electrode 107. The grating-type metal back electrode 107 has been structurally optimized to maintain its efficient collection of charge carriers and reflection / diffraction of transmitted light from the front side. Through a specific grating period and opening design, it allows some sunlight to directly enter from the back side of the cell and pass through the back electrode into the cadmium telluride absorption layer 105, thereby achieving bifacial light-receiving and power generation. The transparent conductive layer 103 can be made of materials such as fluorine-doped tin oxide (FTO), tin-doped indium oxide, or aluminum-doped zinc oxide; the window layer 104 is one or more combinations of zinc oxide, zinc oxide doped with magnesium, indium oxide, cadmium sulfide, or cadmium selenide, with a thickness of 10~300 nm; the cadmium telluride absorption layer has a thickness of 0.8~1.0 μm; the back contact layer 106 is made of one or more combinations of zinc telluride, copper-doped zinc telluride, or molybdenum oxide, with a thickness of 3~100 nm. Through the synergistic optical design of the front and rear gratings, effective capture and utilization of incident light from both sides is achieved. In this structure, the guided-mode resonant grating 102 is fabricated on the surface of the substrate 101 using micro-nano fabrication processes such as nanoimprinting, step exposure, wet etching, and reactive ion etching (RIE). The guided-mode resonant grating 102, while maintaining its lateral conductivity, utilizes the first period to modulate the incident light with the wave vector, exciting the surface electromagnetic mode and enhancing the local field, thereby significantly improving the light capture efficiency and photogenerated carrier generation rate of the cadmium telluride absorber layer 105 in the long wavelength (700~860nm). The window layer 104 not only achieves pn junction band alignment but also serves as an interface passivation layer; the back contact layer 106 provides a stable ohmic contact and efficient selective carrier transport.
[0044] This invention also provides a method for preparing a bifacial cadmium telluride thin-film solar cell, comprising the following steps: A substrate 101 is provided, preferably a glass substrate; A mode-guided resonant grating 102 is fabricated on substrate 101; A transparent conductive layer 103 is deposited on the surface of the guided mode resonant grating 102 and the substrate 101, which can be achieved by chemical vapor deposition, sputtering or wet spraying processes. A window layer 104 and a cadmium telluride absorber layer 105 are sequentially deposited on the transparent conductive layer 103, and the cadmium telluride absorber layer 105 is then treated with cadmium chloride and annealed. The deposition methods for the window layer 104 include magnetron sputtering, thermal evaporation, near-space sublimation, and vapor transport. The deposition methods for the absorber layer include gradient magnetron sputtering, vacuum thermal evaporation, near-space sublimation, and vapor transport. The cadmium chloride treatment can be performed by thermal evaporation, spraying, roller coating, or immersion. The cadmium chloride annealing temperature is 300~550℃, and the time is 10~50min. A back contact layer 106 is prepared on the annealed cadmium telluride absorber layer 105, which can be formed by thermal evaporation, magnetron sputtering or atomic layer deposition. A grating-type metal back electrode 107 is fabricated on the back contact layer 106, and a cadmium telluride thin-film battery is obtained after annealing. The annealing temperature is 100~300℃ and the time is 10~40min. The grating-type metal back electrode 107 can be fabricated by nanoimprinting, wet etching or reactive ion etching. The period of the grating-type metal back electrode 107 is configured to achieve phase matching with the propagation constant of the guided mode excited by the guided mode resonant grating 102 in the cadmium telluride absorption layer 105.
[0045] In one specific implementation, the grating-type metal back electrode 107 is fabricated using a low-temperature magnetron sputtering process, with the substrate temperature controlled below 80°C. Compared to the high-temperature conditions (typically above 200°C) required for conventional fabrication of transparent conductive oxides (such as ITO), this low-temperature process effectively suppresses the generation of interface defects and the interdiffusion of metal impurities, thereby reducing the resulting non-radiative recombination losses and improving the electrical performance of the back electrode interface and the overall device efficiency.
[0046] The following detailed description of examples of the present invention is exemplary and is used only to explain the present invention, and should not be construed as limiting the present invention.
[0047] Example 1 A double-sided cadmium telluride thin-film solar cell, the stacked structure of which is as follows: Glass substrate: Sodium-calcium glass; Mode-guided resonant grating: A grating structure made of silicon nitride (Si3N4); Transparent conductive layer: Fluorine-doped tin oxide (FTO); Window layer: Cadmium selenide (CdSe); Cadmium telluride absorber layer; Back contact layer: Copper-doped zinc telluride (ZnTe:Cu); Grating-type metal back electrode: aluminum (Al) grid electrode.
[0048] The method for preparing this double-sided cadmium telluride thin-film solar cell includes the following steps: Step 1: Deposit silicon nitride film Silicon nitride films were deposited on glass substrates using plasma-enhanced chemical vapor deposition (PECVD). a) The reactant gas ratio is SiH4:NH3 = 1:6, and the radio frequency power is 400 W; b) The deposition temperature is 300℃, the film thickness is 100 nm, and the internal stress of the film is controlled at ≤180 MPa; c) The glass substrate interface was pretreated with H2 plasma before deposition (flow rate 50 sccm, power 100 W, time 5 min).
[0049] Step 2: Fabrication of Si3N4 guided-mode resonant grating Cylindrical gratings were fabricated on a glass substrate with deposited silicon nitride using a nanoimprint lithography process. a) Hard template preparation Clean the silicon substrate; Spin-coating polymethyl methacrylate (PMMA) electron beam photoresist onto a cleaned silicon substrate; Electron beam exposure was used, with an exposure dose of 200 μC / cm. 2 10 nA beam current; Photoresist development: Pre-dry at 110℃ for 1 min, then immerse in MIBK (methyl isobutyl ketone):IPA (isopropanol) = 1:3 developer solution for 1 min, then immerse in IPA (isopropanol):DI water (deionized water) = 3:1 emergency stop solution at 0~4℃ for 30 seconds to terminate the reaction, and finally blow dry with dry nitrogen gas.
[0050] Inductively coupled plasma (ICP) etching was used: the etching gas was CHF3:SF6 = 2:1 (flow rates of 40 sccm and 20 sccm respectively), and the radio frequency power was 100 W. Remove the residual photoresist to obtain a silicon hard template with the target pattern.
[0051] b) Soft template preparation The aforementioned silicon hard template was subjected to oxygen plasma cleaning; The polydimethylsiloxane (PDMS) prepolymer and curing agent were mixed at a mass ratio of 10:1 and then heated at 10... -3 Degassing under vacuum for 10 minutes using Torr; Pour the mixture onto the template surface and cure it on a 75℃ hot plate for 2 hours. Demolding yields a PDMS soft template.
[0052] c) Imprinting and curing The glass substrate with deposited silicon nitride was treated with hexamethyldisilazane (HMDS) for adhesion enhancement (110℃, 5min), then spin-coated with UV imprinting adhesive STU-7 (adhesive layer thickness approximately 250 nm), and then covered with a PDMS soft template. Imprinting and curing were performed under 0.3 MPa pressure and 365 nm UV light.
[0053] d) Graphic transfer and cleaning The imprinted substrate was placed on a 0°C cold stage for 10 minutes to facilitate demolding. Subsequently, CF4 / Ar plasma etching was used to transfer the pattern to the Si3N4 layer at an etching rate of approximately 50 nm / min. After etching, residual imprinting adhesive was removed, ultimately yielding a Si3N4 columnar grating structure with a period of 500 nm, a diameter of 150 nm, and a height of 100 nm, i.e., a guided-mode resonant grating.
[0054] Step 3: Deposit a transparent conductive layer A fluorine-doped tin oxide (FTO) layer was deposited on a glass substrate with a grating structure using chemical vapor deposition. The precursors were SnCl4 and CHF3 (molar ratio 1:0.03), the carrier gas was N2 (2000 sccm), the deposition temperature was 480±5℃, and the pressure was 0.8 kPa, resulting in a FTO transparent conductive layer with a thickness of approximately 400 nm.
[0055] Step 4: Deposition of window layer Cadmium selenide (CdSe) window layer was deposited on the FTO surface using a near-space sublimation method: The source temperature was 680℃ and the substrate temperature was 550℃, resulting in a CdSe layer with a thickness of 80 nm.
[0056] Step 5: Deposit the absorption layer Similarly, a cadmium telluride (CdTe) absorber layer was deposited on the window layer using the near-space sublimation method: The source temperature is 650℃, the substrate temperature is 550℃, and the deposition thickness is 850 nm.
[0057] Step 6: Cadmium chloride treatment and annealing The cadmium telluride absorber layer was sprayed with cadmium chloride and then annealed at 390℃ for 30 min to optimize the grain structure and interface properties.
[0058] Step 7: Deposit back contact layer A copper-doped zinc telluride (ZnTe:Cu) back contact layer was deposited on the surface of the cadmium telluride absorber layer using magnetron sputtering. With a sputtering power of 0.6 kW and an Ar gas flow rate of 45 sccm, a ZnTe:Cu layer with a thickness of 30 nm was deposited at room temperature.
[0059] Step 8: Annealing of the back contact layer The ZnTe:Cu back contact layer was annealed at 300℃ for 15 min to improve its electrical contact performance.
[0060] Step 9: Fabrication of grating-type metal back electrode Aluminum grating electrodes were fabricated on the surface of the back contact layer using nanoimprinting and lift-off processes. a) Spin-coating OCL-200 UV photoresist and imprinting using a PDMS soft template to define a gate pattern with a period of 700 nm; b) Under the condition that the substrate temperature is ≤80℃, an aluminum layer with a thickness of 130 nm is deposited by magnetron sputtering; c) The photoresist and excess aluminum layer are removed by a stripping process to finally obtain an aluminum grating back electrode with a linewidth of approximately 210 nm and a period of 700 nm.
[0061] Example 2 The preparation method is the same as in Example 1, except that in step 2d, a cylindrical Si3N4 guided mode resonant grating with a diameter of 200 nm is prepared by controlling the nanoimprinting and plasma etching processes. In step 9c, the linewidth of the grating-type metal back electrode layer 107 obtained is 280 nm.
[0062] Example 3 The preparation method is the same as in Example 1, except that in step 2d, a cylindrical Si3N4 guided mode resonant grating with a diameter of 250 nm is prepared by controlling the nanoimprinting and plasma etching processes. In step 9c, the linewidth of the grating-type metal back electrode layer 107 obtained is 350 nm.
[0063] Example 4 The preparation method is the same as in Example 1, except that in step 2d, a cylindrical Si3N4 guided mode resonant grating with a diameter of 250 nm is prepared by controlling the nanoimprinting and plasma etching processes. In step 9c, the final obtained grating-type metal back electrode layer 107 has a linewidth of 500 nm and a period of 500 nm.
[0064] Comparative Example 1 The preparation method is the same as in Example 1, except that a fluorine-doped tin oxide (FTO) transparent conductive layer is directly deposited on a soda-lime glass substrate using chemical vapor deposition, without introducing a grating structure. A cadmium telluride absorber layer was prepared by near-space sublimation method, with a source temperature of 780℃ and a substrate temperature of 650℃. The resulting cadmium telluride absorber layer had a thickness of 3.5µm and was subsequently annealed with cadmium chloride. An 80 nm thick aluminum layer was deposited as the back electrode using magnetron sputtering to form a continuous planar structure.
[0065] Comparative Example 2 The preparation method is the same as in Example 1, except that a fluorine-doped tin oxide (FTO) transparent conductive layer is directly deposited on a soda-lime glass substrate using chemical vapor deposition, without introducing a grating structure. A cadmium telluride absorber layer was prepared by near-space sublimation method, with a source temperature of 780℃ and a substrate temperature of 650℃. The resulting cadmium telluride absorber layer had a thickness of 800 nm and was subsequently annealed with cadmium chloride. An 80 nm thick aluminum layer was deposited as the back electrode using magnetron sputtering to form a continuous planar structure.
[0066] Test case For the bifacial cadmium telluride thin-film solar cells prepared in Examples 1-4 and Comparative Examples 1-2, under standard test conditions (AM 1.5G, 1000 W / m²), 2 At 25℃, comprehensive photoelectric performance characterization was performed using a solar simulator and IV testing system. Tests included: measuring the back electrode transmittance (Trear) to assess back-side light incidence; recording the open-circuit voltage (Voc) to analyze carrier separation and recombination states; obtaining the short-circuit current density (Jsc) to quantify light absorption and carrier collection efficiency; extracting the fill factor (FF) from the IV curve to assess internal resistance loss; and testing the front efficiency (ηfront) and back efficiency (ηrear) to determine the bifacial power generation performance of the battery. Characterization results are shown in Table 1. For the specific structures of Comparative Examples 1-2, please refer to [reference needed]. Figure 2 .
[0067] Table 1
[0068] Based on the above data, it can be seen that the embodiments of the present invention effectively achieve optical field modulation and carrier management in the ultrathin cadmium telluride absorption layer through the synergistic design of the front interface guided mode resonant grating and the grating-type metal back electrode: the short-circuit current density (Jsc) of Examples 1-4 is significantly higher than that of the ultrathin comparative example 2 without a grating structure, with the Jsc of Example 2 reaching 28.9 mA / cm². 2Compared to Comparative Example 2, the efficiency is improved by approximately 12%, demonstrating that this structure can significantly enhance long-wavelength photon capture and suppress light escape. Simultaneously, all embodiments achieved effective bifacial power generation, with the highest back-side efficiency (ηrear) reaching 17.6% (Example 3), and the front-side efficiency (ηfront) being extremely close to that of Comparative Example 1 (18.9%), which uses a conventional thick layer (3.5 μm). This indicates that while reducing the absorber layer thickness by approximately 75%, the present invention not only significantly reduces material consumption but also approaches or even surpasses the photoelectric performance of traditional thick batteries, endowing the battery with efficient bifacial operation capabilities. This provides a technical solution for the application of cadmium telluride batteries in scenarios such as building-integrated photovoltaics (BIPV) that combines high performance, low cost, and bifacial advantages.
Claims
1. A double-sided cadmium telluride thin-film solar cell, characterized in that, include: The cadmium telluride absorber layer has a thickness of 0.8~1.0 μm; A guided-mode resonant grating is disposed on the front side of the cadmium telluride absorption layer, and the guided-mode resonant grating has a first period; The first period is configured to couple the solar spectrum incident from the front side into a guided mode propagating in the cadmium telluride absorption layer through the guided mode resonance effect; the phase matching equation is determined by the guided mode resonance condition. A grating-type metal back electrode is disposed on the back side of the cadmium telluride absorption layer, comprising periodically alternating metal grating lines and light-transmitting gaps, wherein the grating-type metal back electrode has a second period. The second period is configured to be phase-matched with the propagation constant of the guided mode based on the reverse coupling phase matching condition, so as to generate reverse coupling to the guided mode, thereby forming an optical resonant cavity together with the cadmium telluride absorption layer, the guided mode resonant grating and the grating-type metal back electrode to enhance light absorption. The first period Λ of the guided mode resonant grating front Based on the optimized determination of the guided mode resonance condition, its phase matching equation is: Where: β guided Let n be the propagation constant of the excited guided mode, which is determined by both the waveguide structure and material properties. This constant can be obtained by solving the eigenvalue problem of Maxwell's equations under specific boundary conditions. k0 = 2π / λ is the wave vector of the incident light in vacuum, and n is the propagation constant of the excited guided mode. eff θ is the effective refractive index of the guided mode; θ is the incident angle; m is the diffraction order, usually taken as m=±1; The second period Λ of the grating-type metal back electrode rear Determined based on the reverse coupling phase matching condition: Where n is the diffraction order, usually taken as n=±1.
2. The double-sided cadmium telluride thin-film solar cell according to claim 1, characterized in that, The first period is 300~500nm; the second period is 600~750nm.
3. The double-sided cadmium telluride thin-film solar cell according to claim 1, characterized in that, The guided mode resonant grating is a hexagonal cylindrical grating.
4. The double-sided cadmium telluride thin-film solar cell according to claim 3, characterized in that, The height of the hexagonal cylindrical grating is 100~200nm and the diameter is 150~300nm.
5. The double-sided cadmium telluride thin-film solar cell according to claim 1, characterized in that, The material of the guided mode resonant grating is selected from silicon nitride or silicon dioxide.
6. The double-sided cadmium telluride thin-film solar cell according to claim 1, characterized in that, The grating-type metal back electrode has a parallel grating line structure; wherein the linewidth of the metal grating line is 210~500nm and the thickness is 50~150nm.
7. The double-sided cadmium telluride thin-film solar cell according to claim 1, characterized in that, The material of the metal grid wire is selected from one or more of molybdenum, aluminum, chromium, silver, copper, and nickel.
8. The double-sided cadmium telluride thin-film solar cell according to claim 1, characterized in that, Also includes: A transparent conductive layer and a window layer are sequentially stacked on the front side of the cadmium telluride absorber layer; A back contact layer disposed on the back side of the cadmium telluride absorber layer; The guided mode resonant grating is disposed on the surface of the transparent conductive layer away from the cadmium telluride absorption layer.
9. A method for preparing a double-sided cadmium telluride thin-film solar cell as described in any one of claims 1 to 8, characterized in that, Includes the following steps: Provide a substrate; A mode-guided resonant grating is formed on the substrate; A transparent conductive layer is deposited on the guided-mode resonant grating and the substrate; A window layer and a cadmium telluride absorption layer are sequentially deposited on the transparent conductive layer, and the cadmium telluride absorption layer is treated with cadmium chloride and annealed. A back contact layer is formed on the cadmium telluride absorber layer after annealing; A grating-type metal back electrode is formed on the back contact layer; The period of the grating-type metal back electrode is configured to match the phase of the propagation constant of the guided mode excited by the guided mode resonant grating in the cadmium telluride absorption layer.
10. The preparation method according to claim 9, characterized in that, The steps for forming the grating-type metal back electrode include: On the surface of the back contact layer, a metal material is deposited by magnetron sputtering at a substrate temperature not exceeding 80°C to form the grating-type metal back electrode.
Citation Information
Patent Citations
Silicon-based thin-film solar cell with double-layer split grating structure
CN112909104A
Infrared photoelectric detector and manufacturing method thereof
CN120640811A
Cadmium telluride solar cell and preparation method thereof
CN121174605A
Symmetric grating-based angle selection device with reciprocity
CN121522784A